High-accuracy effective density measurements of sodium methanesulfonate and aminium chloride nanoparticles using a particulate calibration standard. Issue 4 (3rd April 2023) - Perraud, Véronique; Smith, James N.; Olfert, Jason
Abstract: Methanesulfonate and aminium salts are commonly found in ambient nanoparticles and are often used as calibration standards. However, the effective densities of the particles generated from these standards are required if they are to be used to calibrate aerosol mass spectrometers or to estimate hygroscopic growth factors from electrodynamic balance experiments. A centrifugal particle mass analyzer and scanning mobility particle sizer were used in tandem (CPMA-SMPS) to measure the effective density of five salts. The effective densities were determined to be: sodium methanesulfonate, 1474 ± 13 kg m −3 ; methylammonium chloride, 1236 ± 29 kg m −3, monoethanolamine hydrochloride, 1136 ± 26 kg m −3 ; 1, 4-diaminobutane dihydrochloride, 1135 ± 33 kg m −3 ; and NaCl was found to have a size-dependent effective density due to its non-spherical shape. It is also shown how Santovac® vacuum pump oil can be used to accurately calibrate the CPMA-SMPS system for particles less than 100 nm in diameter, which is a size range that has been problematic for calibration techniques relying on polystyrene latex spheres. Copyright © 2023 American Association for Aerosol Research